Co-teaching that works : structures and strategies for maximizing student learning - Beninghof, Anne M. (San Francisco, CA : Jossey-Bass, 2012)
'Guaranteed success for the co-taught classroom for the increasing number of teachers working in co-taught classrooms, this book provides practical ideas for defining teacher roles, planning lessons, providing effective instruction, and maximizing the value of each team member. Former co-teacher and national presenter Anne Beninghof shares stories, and real-life co-taught lesson examples that emphasize creative yet time-efficient instructional strategies that lend themselves beautifully to the co-taught classroom. Teachers and instructional leaders at all levels and in a wide variety of content areas will find this book replete with valuable co-teaching guidance so that success is guaranteed. Offers tips for effective teaching strategies for every type of team teaching situation imaginable Includes guidelines for successful team-teaching with specialists in technology; literacy; occupational/physical therapy; special education; speech-language therapy; ELL; gifted The author is an internationally recognized consultant and trainer This user-friendly, comprehensive book is filled with concrete ideas teachers can implement immediately in the classroom to boost student learning and engagement'--Provided by publisher.
An overview of co-teaching -- Relationship building: common challenges and effective solutions -- Implementations: common challenges and effective solutions -- The duet model -- Lead and support model -- Speak and add model -- Skill groups model -- Station model -- Learning style model -- Parallel teaching model -- Adapting model -- Complementary skills model -- Co-teaching with a technology specialist -- Co-teaching with a special education teacher -- Co-teaching with a speech/language pathologist -- Co-teaching with and occupational or physical therapist -- Co-teaching with a paraeducator -- Co-teaching with a gifted specialist -- Co-teaching with a literacy specialist -- Co-teaching with an ELL specialist -- Conclusion: evolving partnerships.
Includes bibliographical references and index.
Keywords: Teaching teams; Classroom management; EDUCATION / Teaching Methods & Materials / General